Model of Home Care Management for Patients with Coronavirus Disease 2019 in Urban Communities - Suksai, Narong; Leetongdeesakul , Songkramchai; Thiabrithi , Surasak (Journal of Nursing, Siam University, 2023)
This action research was aimed to examine the home care management model for COVID-19 patients in urban communities. The target population in this study included people who have involved in home caring for patients with COVID-19, COVID-19-infected patients and caregivers, a total of 258 people. Data collection was conducted quantitatively using questionnaires, interviews, and quantitative data analysis. The statistics implemented included frequency, percentage, mean, and standard deviation. Content analysis was performed for qualitative data. The results found that the home care management model for COVID-19 patients in urban communities consisted of 1) cognitive process of context, problems, and actual needs of the communities, 2) adjusted service provision in line with basic needs, 3) preparedness to implementation and dealing with the COVID-19 outbreak situation, including personnel, medicines, medical supplies, including effective service behavior of medical personnel, 4 ) the use of technology or social media to communicate with patients in a fast manner. The outcomes of home care management model for COVID-19 patients demonstrated that the patients’ self-care behavior was at the ‘very good’ level.